From Pest to Profit—The Potential of Shipworms for Sustainable Aquaculture - Willer, David F.; Aldridge, David C. (Frontiers in Sustainable Food Systems, 2020)
We face a food crisis. Suboptimal diet is the biggest cause of death worldwide, food production the biggest greenhouse gas emitting sector, and by 2050 an extra 2.5 billion people need affordable nutrition. Current farming systems will fail to tackle this crisis, and there is an urgent need to diversify global food production and find effective solutions in currently underexploited food sectors. Shipworms, or shell-less Teredo clams, could prove a highly valuable component of such solutions. Historically viewed as a marine pest, they have unique physiological characteristics which make them an ideal food source, including exceptionally fast growth rates, the ability to feed on waste wood or sustainable microalgae, and a high protein and omega 3 content. Today only a select few traditional cultures in the Philippines consume shipworms, but there is considerable opportunity to develop mechanisms to farm shipworms and provide a sustainable, nutrient rich, affordable food source. This will require significant challenges to be overcome, ranging from fundamental research to industry development to food processing and marketing. Leveraging new innovations in breeding, aquaculture feeds, growth systems, food processing methodologies and consumer engagement can however offer powerful solutions, and could help turn what was once a maritime villain into a nutritional savior.